Inflammatory rhabdomyoblastic tumor, pheochromocytoma, and pulmonary hamartoma in a patient with neurofibromatosis type 1: a case report - Otto Jokelainen; Heidi Myllykangas; Katri Rajala; Jarkko Marttila; Reijo Sironen (BMC, 2024)
Abstract Background Inflammatory rhabdomyoblastic tumors are relatively recently recognized soft tissue tumors with a low malignant potential. Here, we present a case of concurrent inflammatory rhabdomyoblastic tumor (IRMT), adrenal pheochromocytoma, and pulmonary hamartoma in a patient with neurofibromatosis type 1 (NF1). To our knowledge, this is the first time that this constellation of tumors has been described in the literature. Case presentation A female patient in her late 20s with known NF1 was diagnosed with an inflammatory rhabdomyoblastic tumor, pheochromocytoma, and pulmonary hamartoma in a short succession. IRMT was found to harbor a near-haploid genome and displayed a typical immunohistochemical profile as well as a focal aberrant p53 expression pattern. Conclusions This case report strengthens the theory that defects in the tumor suppressor NF1 play a central role in the pathogenesis of inflammatory rhabdomyoblastic tumors and that IRMT may be part of the spectrum of neurofibromatosis type 1 related tumors.